The Impact of Occupational Stress Factors to Job Stress in Housekeeping Department of Hotel ABC - Anthony Lilianto Lie (iBuss Management, 2015)
The increase of tourist coming to Indonesia makes many hotels in the industry compete to attract the customer. However, the consumers become more sharp and selective to choose the hotel where they want to stay. Easily accessed information and review about hotel makes the management of the hotel wants to give the best impression to consumer. The heavy demand from management and customers as well as the increase number of work will increase the stress level of the employees. The management cannot ignore the stress level of the employees. Managing the stress level of the employees will help Hotel ABC to keep performance of the employees at utmost level. This research was conducted in Housekeeping department of Hotel ABC by distributing questionnaires to 58 employees. The sampling method used was simple random sampling. The data were analyzed using Multiple Linear Regression Analysis. The results show that work relationship, work overload, job security, and job characteristics do not pass validity and reliability test. The rest of independent variables passed the validity and reliability test, but do not have significant impact towards job stress simultaneously or individually. Keyword: Human Resource, Job Stress